The problem of violence in schools And the role of social work in dealing with it - Nizar Abdul-Sada Al-Nasser , Assi.Prof. Dr (lark, 2022)
This study attempted to investigate a school problem prevailing in many schools, it was found through the conclusions that were reached that there are many factors and causes behind the phenomenon of school violence, and they were discussed in the theoretical study, as was the role of social service. The social worker in this field and to what extent does the presence of the social worker contribute to social rehabilitation and help students face the obstacles and problems facing them. In this study many scientific concepts mentioned in the research were defined, and the researcher also indicated the most important causes and factors leading to school violence The research revealed the spread and increase of the phenomenon of school violence in many schools and its various forms, including verbal, physical and psychological violence, and the negative impact of that on the student’s academic achievement on the one hand and on the extent of continuing study and learning on the other hand